Pengaruh Ethical Sensitivity, Love Ofmoney, Machiavellian dan Gender Terhadap Persepsi Etis Mahasiswa Akuntansi (Studi Empiris Pada Mahasiswa Perguruan Tinggi Swasta di Denpasar) - I Made Yuda Adnyana; I Gusti Ayu Intan Saputra Rini; A.A Sri Purnami (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2022)
This research aims to recognize ethical sensitivity, love of money, machiavellian and gender to the ethical perceptions of accounting students. The population in the research was a semester VII accounting student at a Private College in Denpasar with 94 respondents as a sample. Multiple Linear Regression, Coefficient of Determination, Test t and Test F are data analysis techniques. The results of the study said that: (1) ethical sensitivity has a positive impact on the ethical perception of accounting students, where regression coefficients are obtained 0.314 and sig 0.000. (2) love of money has a negative impact where regression coefficients are obtained of - 0.266 and sig 0.021. (3) Machiavellian negatively impacts the ethical perception of accounting students, where regression coeffesiens - 0.250 and sig 0.031. (4) gender negatively impacted regression by 0.183 and sig 0.017. The advice that can be given by researchers is a Private College in Denpasar in improving the ethical perception of accounting students expected to pay attention to ethical sensitivity, love of money, machiavellian and gender.